Assessment and comparison of fatigue in shift workers of a rolling mill and a steel production company - marziye Abbassinia; farogh Mohammadian; mohammadreza Monazam; somaye MahmoodKhani; mahdi Asghari; navid Ghaemian (طب کار)
Background: High levels of fatigue in the workplaces can lead to reduced productivity, and increase the risk of accidents and injuries. Purpose of this study was to assess and compare the fatigue levels among fixed-dayshift and rotating-shift workers of a rolling mills and steel production company in tehran. Methods: The study included 180 workers with fixed- and rotating-shift schedules. The method involved in our survey data collection was using standard questionnaires by face-to-face surveys. Results: Results showed that maximum level of fatigue for both groups is 4. Fatigue level between fixed-day shift and rotating-shift workers was statistically significant the degree of fatigue was higher in rotating shift workers. All symptoms associated fatigue in rotating shift workers were more severe than other, and statistically was significant. Comparison between tasks showed the most exhausting task is warehouse. Conclusion: Results show that level of fatigue is high in the company's personnel, so adopting proactive measures such as reducing working hours, doing regular rest and exercise during working time, paying sufficient attention to humanitarian needs and improving work system can be helpful.